Harm reduction stories: leveraging graphic medicine to engage veterans in substance use services within the VA - Leah H. Harvey; Westyn Branch-Elliman; Jacqueline Boudreau; Samantha K. Sliwinski; Allen L. Gifford; Minh Q. Ho; Elizabeth Dinges; Justeen Hyde (BMC, 2023)
Abstract Background Harm reduction strategies can decrease morbidity and mortality associated with substance use. Various barriers limit conversation around substance use between clinicians and patients. Graphic medicine techniques can inform and encourage patient-centered conversations about substance use. We describe the co-development of a harm reduction-focused graphic medicine comic that depicts the infectious risks associated with injection drug use and patient-centered approaches to providing education about potential risk mitigation strategies. Methods We formed a co-design group of veterans with lived experience with substance use, physicians, health services researchers, and community-based harm reduction leaders. Over the course of ten sessions, the co-design team developed a storyline and key messages, reviewed draft content and worked with a graphic designer to develop a comic incorporating the veterans' input. During each session, co-design leads presented drafts of the comic and invited feedback from the group. The comic was edited and adapted via this iterative process. Results The comic depicts a fictionalized clinical vignette in which a patient develops an injection-related abscess and presents to their primary care provider. The dialogue highlights key healthcare principles, including patient autonomy and agency, and highlights strategies for safer use, rather than emphasizing abstinence. Feedback from co-design group participants highlights lessons learned during the development process. Discussion Graphic medicine is ideally suited for a patient-centered curriculum about harm reduction. This project is one of several interventions that will be integrated into VA facilities nationally to support incorporation of harm reduction principles into the care of persons who inject drugs.